2016
DOI: 10.5935/0004-2749.20160090
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between outer retinal destruction and choroidal changes in cone dystrophy?

Abstract: Approved by the following research ethics committee: GATA Medical School (# 2015-KAEK-45). ABSTRACT Purpose:The aim of the present study was to use enhanced depth imaging optical coherence tomography (EDI-OCT) to investigate choroidal changes in patients with cone dystrophy (CD) and to correlate these findings with clinical and electroretinography (ERG) findings. Methods: This case-control study included 40 eyes of 20 patients with CD and 40 eyes of 40 age-and refraction-matched healthy individuals. Choroidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…[4,5,19] However, other studies did not find such correlations. [10,13,16,18] This difference may be due to a higher number of subjects and a longer duration of ocular symptoms in the present study. Ayton et al [4] reported that choroid becomes thinner with increasing duration of RP symptoms, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…[4,5,19] However, other studies did not find such correlations. [10,13,16,18] This difference may be due to a higher number of subjects and a longer duration of ocular symptoms in the present study. Ayton et al [4] reported that choroid becomes thinner with increasing duration of RP symptoms, which is consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 68%
“…[12] Measurement of the choroidal thickness can be informative in determining the pathophysiology and natural course of IRDs. [13][14][15] Some studies have reported a significant reduction in the choroidal thickness in RP, [4,15,16] Stargardt disease, [17] and cone dystrophy [18] when compared with healthy controls. However, no difference was observed in other studies.…”
Section: Introductionmentioning
confidence: 99%
“…Choroid thinning has been described in IRDs, such as RP, rod-cone dystrophies and CDs, using SD-OCT, which is probably secondary to a loss of photoreceptor and RPE cells. Vascular endothelial growth factor, which is produced by RPE cells, has been demonstrated to participate in choroidal maintenance; therefore, it has been suggested to play a role in choroidal atrophy [33][34][35]. In addition, a reduction of the choriocapillaris density has been described in patients affected by RP using OCTA [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal thinning has also been reported in RP 221,222 and cone dystrophy. 223 Sabbaghi et al recently reported that the choroidal thinning pattern was different when comparing patients with STGD1, RP, Usher syndrome and cone dystrophy. They found that patients with RP and Usher syndrome had a significantly thinner choroid than patients with STGD1 and cone dystrophy which led the authors to suggest that IRDs might have different alterations to blood flow 224 or it may be that there is secondary reduction to flow in more severe diseases.…”
Section: Icga In Stgd1mentioning
confidence: 99%